National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages We cannot assume, however, that reductions in the rate of mortality always correspond with an increase in positive health. We must recognise that the physical standard of a great part of the nation remains deplorably low. The annual loss of work, energy, and happiness through avoidable ill-health mounts up to a stupendous sum in comparison with what we spend on preventive medicine and medical research. The mass evacuation of children from our crowded cities to the smaller towns and the countryside during the present war has forced the people of Britain to realise, as never before, how shameful and wasteful are the conditions under which a great number of their countrymen and women are still condemned to live. When this war began the nation's food policy was not based on the food requirements of the people as a whole, but reflected rather the interests of trade. Nor is the nation's health policy nationally designed or nationally controlled to meet the health requirements of the whole nation. The lower the family income falls, the lower, generally speaking, is the standard of health. The infant mortality rate has been reduced to some extent in all classes of society, but the richest class has benefited nearly twice as much as the great bulk of the nation from the new knowledge that has made this reduction possible.* The infant mortality-rate among the working class is double what it is in the richest section of the population.** Tuberculosis is twice as prevalent amongst the poor as amongst the well-to-do, and the average stature of the well-to-do is three or four inches greater than among the poor. The lower standard of health amongst the poor is due mainly to surroundings, rather than heredity. Statistics show that, as might be expected, the industrial areas are much less healthy than the countryside, and that in the counties of Durham and Northumberland the death-rate of children between one and two years is double the rate in the South-Eastern Counties outside the London area. We cannot do much to control heredity, but we can control our environment; and, if we will, we can have a health policy, as well as a food policy, based on the requirements of all the people. The war has forced us to move in this direction. The food-rationing policy, for example, whatever its defects, has been such a move. We are now assured by the Minister of Food that the nation in general is better nourished on its war-time diet than it was before the war. What an indictment of pre-war policy this is! It means that the good resulting from improved distribution has out-weighed the injury resulting from the enforced reduction of the national food supply. Will the nation be content to ignore that lesson after the war? Or shall we insist, as to some extent we do insist in war-time, upon there being "bread for all before there is cake for any"? So much for Britain's health record. Now look at Britain's health organisation. The Control of the Health Services Who plans and controls the nation's Health Services? The answer is that a great many authorities are concerned, each controlling a bit, and that no one is in a position to make or direct a coherent plan of health services for the nation as a whole. One might expect that the Ministry of Health would be in a position to do this ; but an outline of the powers now possessed by this Ministry will show that this is not the case. Since 1929, the Ministry of Health has been charged with widely-increased responsibilities in England and Wales ; but many important health services remain under * R.M. Titmuss, Birth, Poverty and Wealth. ** In 1936 the infant mortality rate per 1,000 live births in Glasgow was 109 (which exceeds the rate in Tokio or Buenos Aires). In Gateshead it was 92 ; London, 66; Surrey, 42! 36/H24/40